TANAMAN PAKAN TERNAK SEBAGAI PENGUAT TERAS - Herawati, Tati; Miranti, Miranti (Pastura, 2011)
Research activities have been carried out to study the role of fodder plant terrace in the Canggal village, kecamatan Kledung, kabupaten Temanggung. It is located on a plateau with slope range between 15-45%. Treatment aims were to conserve the slopes land with grass fodder crops by planting terrace with grass. The measurement was done on the soil erosion which belongs to the rorak made on each end of the strip. The results showed that planting in slopes areas with grass strips reduced erosion rate by 26%. With the planting strip of grass, still showed the existence of differences in erosion in different precipitation levels. But with a strip of grass, the rate of erosion on the slope of 30-45% can be pressed to no different than land that has a slope of 15-25%. Technology of strengthening terrace as part of the conservation of wetlands has been adopted by cooperator farmers and growing to non cooperators.
Keywords: conservation; erosion; pasture